“SINCE SINGING IS SO GOOD A THING”. Handbook for Music Teachers and Choir Masters. by GRAHAM HYSLOP. Oxford University Press, Nairobi, 1964. pp. 127. - Tracey, Hugh (International Library of African Music, 1964)
pages: 119-120
Keywords: African Music